(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In this article, in the treatment of experimentally induced aseptic inflammation of the fingers of rabbits, calciummag 2 ml intravenously once every 24 hours only three times, and phenylbutazone-20 intravenously 0.2 ml once every 48 hours only three times a day according to the norm and quantity, it was determined that the red blood cells in the blood increased by 14.8%, the number of leukocytes increased by 1.6%, the amount of hemoglobin increased by 5.7%, the percentage of lymphocytes in the blood increased by 4%. It is noted that this method of treatment reduces inflammatory processes, enhances regeneration processes, and reduces the duration of treatment by 4 days.